Biomass Derived N-doped Carbon Nanoworm for Improved Sodium-ion in Battery Anode. (2018) - Chakraborty, A.; Dutta, P.K.; Ganesh, A.; Mitra, S.
Abstract: A scalable and economic method is demonstrated to synthesis N-doped Carbon Nanoworm (NCNW) by chemical vapor deposition (CVD) using cashew nut shell liquid as precursor and ammonia as carrier gas and N source which is successfully used as anode material for sodium-ion battery (NIB). Carbon anode is synthesized at 850 °C within 1hr; which is comparatively low temperature method as well as rapid than usual methods producing hard Carbon. Wall thickness of as- prepared Nanoworm is ∼10 nm. The unique morphology high inter layer distance of 0.385 nm helps to store more Na-ion by providing more space to them. A reversible discharge capacity of 500 mAh m -2 has been achieved at a constant current rate of 300 mA m -2 even after 70 cycles, while using the synthesized NCNW as anode material for NIB.